Explore the collection / Dallas Museum of Art - Dallas Museum of Art (2015)
[Dt.:] Die Sammlungsgebiete des Dallas Museum of Art (Texas, USA) reichen von der Antike bis zu Werken zeitgenössischer Kunst. Die Werke der Sammlung können in der Onlinedatenbank recherchiert werden. - [Engl.:] The Dallas Museum of Art is an art museum located in Dallas, Texas. The galleries feature a permanent collection of art ranging from ancient to contemporary periods. The collection can be search in the database.